The Internalization of Myths in Enhancing Religiosity in Mahmud Village: A Cognitive Anthropology Approach - Lestari, Riwi Yunia; Rahman, Ika Annisa; Taufiqurrahman, Rafi (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2025)
Religion is a historical and cultural phenomenon that reflects an undeniable absolute belief. Similarly, in terms of its dissemination, within the Sundanese region there is a figure named Raden Haji Abdul Manaf who established unique rules, prohibitions, and traditions in this village. These rules have since become inherited beliefs upheld by the people of Mahmud Village. Today, the community still observes these regulations as stories or circulating myths, yet they continue to be respected. As a formal teaching, religion plays a significant role in shaping religiosity in every ritual performed. Therefore, this study aims to examine how local myths in Mahmud Village are understood by the community and how they contribute to the enhancement of religiosity. The method used is a cognitive anthropology approach with a descriptive qualitative type. This approach explores how individuals organize cultural knowledge, interpret symbols, and associate collective meanings with the myths that develop within their social environment. Consequently, this study finds that the myths that have developed in Mahmud Village are identified not only as carriers of cultural messages but also as containing deep dimensions of religiosity. The people of Village Mahmud are able to internalize these myths as a means of enhancing religiosity by interpreting each myth through Islamic teachings. In fact, Mahmud Village currently provides religious education to children from an early age and continues to preserve the tradition of visiting ancestral graves.